Design and Evaluation of Bisoprolol Fumarate Transdermal Film: A Promising Approach for Cardiovascular Therapy - H. N. Shivakumar; Anilkumar Reddy; Dhruti Avlani; Prajila Alayadan; Avichal Kumar (Journal of the Scientific Society)
Background: The study aimed to prepare and evaluate the transdermal film of bisoprolol fumarate (BF) for chronic management of hypertension as an alternative to conventional oral dosage form. Materials and Methods: The partition coefficient of BF was determined in n-octanol buffer systems. Preformulation screening of permeation enhancers such as Tween 80, sodium lauryl sulfate (SLS), and polyethylene glycol 200 (PEG 200) was assessed. BF-loaded transdermal films were fabricated using polyvinyl pyrrolidone (PVP) and polyvinyl alcohol (PVA) as bioadhesive polymers and PEG 200 as permeation enhancers. The in vitro permeation studies from the film were carried out in Franz diffusion cells across full-thickness rat skin. Result and Discussion: The partition coefficient of BF was found to be 0.89. The in vitro permeation studies indicated that the steady state (SS) flux of BF across full-thickness rat skin was dependent on donor concentration and was found to be 152.29 µg.cm−2.h−1 for donor concentration of 150 mg.ml−1. A flux of 129.9, 131.0, and 167.1 µg.cm−2.h−1 of BF was noted when Tween 80 (10%), SLS (1%), and PEG 200 (10%) were used as enhancers respectively. The film formulation containing PVP:PVA in a ratio of 6:4 has the desirable physicochemical characteristics and resulted in flux 106.41 µg.cm−2.h−1. A transdermal patch of BF measuring ~7.12 cm2 may be required to be able to achieve the desired therapeutic response in humans. Conclusion: The study successfully demonstrated feasibility of developing a transdermal system that would be able to elicit the desired therapeutic response by calculation of the target flux based on drug pharmacokinetics. The system developed would be a value addition for potent drugs that warrant chronic administration in management of cardiovascular diseases.